Structure of insulin-like growth factor 2 (IGF2) gene from striped catfish (Pangasianodon hypophthalmus) - Thi Nguyen Binh, Le; Thi Hoa, Nguyen; Trang, Tran Thi Huyen; Phuong, Nguyen Thanh; Oanh, Kim Thi Phuong (Vietnam Journal of Biotechnology, 2020)
Gene coding Insulin-like growth factor 2 (IGF2) is one of genes relating the growth of many fish species, including striped catfish. In this study, cDNA coding to protein IGF2 was isolated from total RNA extracted from liver tissue of catfish, then was amplified through reverse transcription PCR and standard PCR with IGF2 specific primer pair to generate the 642bp-in-size PCR product. The sequence of this cDNA-IGF2 is similar up to 95% to the cDNA-IGF2 gene sequence of catfish included in family Ictalurus. Based on that sequence, 3 primer pairs were designed to amplify 3 regions of IGF2 gene from genomic DNA extracted from fins of catfish, which have 900bp, 1500bp and 1200bp in length. That 3 regions were sequenced and assembled to give the final sequence with 3387bp in length of IGF2 gene, which includes 4 exons coding to IGF2 protein, and is similar up to 96% to sequence of mRNA coding to IGF2 protein of channel catfish Ictalurus punctatus and that of blue catfish Ictalurus furcatus. Determining the structure of IGF2 gene of striped catfish Pangasianodon hypophthalmus enable us to further examine its function and genetic variation.